2012
DOI: 10.1002/sia.5204
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface composition on Alloy 22 in neutral chloride solutions

Abstract: The composition of anodically grown oxide films on Alloy 22, a Ni‐Cr‐Mo(W) alloy, has been investigated in 5 mol l−1 NaCl at room temperature using X‐ray photoelectron spectroscopy and time‐of‐flight secondary ion mass spectrometry. For applied potentials up to 0.2 V (vs Ag/AgCl (saturated KCl solution)), a Cr(III) oxide barrier layer develops at the alloy/oxide interface accounting for the excellent passivity demonstrated to prevail in this potential region by previous electrochemical impedance spectroscopy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
5
28
0
Order By: Relevance
“…It has been demonstrated previously [41][42][43] that the PDM can readily explain the observations of the passive state on Alloy-22. Characterization work 41,[44][45][46] has demonstrated that the passive film on Alloy-22 has a distinct layered structure with the inner layer primarily comprising Cr(III) oxide, so it is assumed in the optimization that point defective Cr 2 O 3 is the principal composition of the barrier layer. Fig.…”
Section: Results and Analysis By Numerical Optimizationmentioning
confidence: 99%
“…It has been demonstrated previously [41][42][43] that the PDM can readily explain the observations of the passive state on Alloy-22. Characterization work 41,[44][45][46] has demonstrated that the passive film on Alloy-22 has a distinct layered structure with the inner layer primarily comprising Cr(III) oxide, so it is assumed in the optimization that point defective Cr 2 O 3 is the principal composition of the barrier layer. Fig.…”
Section: Results and Analysis By Numerical Optimizationmentioning
confidence: 99%
“…This suggests the kinetics of film growth are dominantly controlled by the Cr and Mo contents, as observed previously for other Ni-Cr-Mo alloys. [38][39]41 For Ni-Cr-Mo alloys, [38][39]41 the oxide film owes its passivity to its Cr/Mo content, which enforces the formation of an inner Cr(III) oxide barrier layer and an outer, dominantly hydroxide, Mo(VI) layer. With increasing temperature, the evolution in film properties was shown to involve two counterbalancing influences: an increase in overall film thickness, which would be expected to improve passivity, and a decrease in Cr/Mo content, which would be expected to degrade passivity.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The composition of the passive films formed on the Ni-Cr-Mo alloys has been characterized by using different methods such as atomic force microscopy (AFM), time of flight secondary ion mass spectrometry (ToF-SIMS), and X-ray photoemission spectroscopy (XPS). These studies indicated that the composition of the passive films depends on many variables such as anodic potential, presence of aggressive anions, pH and aerating conditions [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 98%